International perspectives in online instruction - Hoffman, Jaimie; Blessinger, Patrick (Emerald Publishing Limited, 2021)
Online learning has been one of the fastest growing areas of educational technology over the past few decades. With a rise of new online colleges and universities due to the Covid-19 global pandemic, as well as the adoption of online learning in traditional institutions, the adoption rate of online learning has moved from an optional service to a mandatory one, requiring higher educational institutions to completely rethink the nature of teaching and learning and how it can be provisioned to meet the needs of students, institutions, and society. This volume considers the technology implementation, faculty training and professional development, and adjustments of university and departmental budgeting required to meet this seismic and momentous challenge. Focusing on effective practices in online teaching, this volume of Innovations in Higher Education Teaching and Learning begins with discussing the use of videos in online teaching and then pivots to consider methods for supporting and managing faculty who teach online. From there, authors focus in on different aspects of the online learning experience including lurking, student engagement, cultural implications for online instruction. Understanding that the greatest challenge for higher education institutions has been not so much how to implement online teaching and learning, but how to do it effectively, the collection closes with an analysis of online course syllabi and effective methods for facilitating tutoring online.
Includes index.
Keywords: Internet in higher education.; Telecommunication in higher education.; Distance education.; Education, Distance, Open & Online Education.; "Open learning, home learning, distance education".; elektronické knihy; electronic books